Comparison of State-owned and Private-owned Emerging Market Enterprises’ Internationalization: Case Studies of Chinese State-owned SAIC Motor’s and Private-owned Geely’s Cross-border Acquisitions. - ZHANG, JIANQIAO (2015)
This research examines the internationalisation activities of firms from emerging economies. By integrating traditional theories with institutional-based view and its three pillars, this study allow us to examine how the government influence international expansion of firms with different ownership structure (state-owned and private-owned) vertically (with government level) and horizontally (with regional specific marketization). The study also highlights different motives of internationalisation for state-owned and private-owned enterprises.